The hymn of Saint Martin by Murmellius - Tuhári, Attila (Verbum – Analecta Neolatina, 2017)
The present paper attempts to map the allusions between Johannes Murmellius of Roermond’s Saint Martin Hymn and the works of Sulpicius Severus about the poets, Horace and Ovid. The results of the examination reveal that Murmellius wished to make his work an integral part of the literary tradition by reflecting on ancient and supposedly contemporary poems.